Comparative study on the effect of EGCG and wheat grass together with mental and physical activities against induction of Alzheimer's disease in both isolated and socialized rats - Mona G. Khalil; Azza A. Ali; Soha Osama Hassanin; Aya H. Al-Najjar; Soumya Ghosh; Maha Osama Mahmoud (Elsevier, 2022)
Background: Alzheimer's disease (AD) is the most common cause of dementia where symptoms gradually deteriorate over years. We previously reported that social isolation exacerbates memory loss while mental and physical activities maintain cognitive functions. Epigallocatechin-3-gallate (EGCG), a natural chelator, and wheatgrass, natural antioxidant could provide CNS health-promoting effects. Purpose: The study aimed to investigate the combined effects of EGCG and wheatgrass together with mental and physical activities against AD in socialized and isolated conditions. Study design: Rats were classified into socialized and corresponding isolated groups. Methodology: Eight groups of rats (4 socialized and 4 isolated) were exposed to mental and physical activities using Swimming test and Y-maze (each for one time/week) during four weeks of the experiment. Two groups of both socialized and isolated were normal while the others (AD model) received daily AlCl3 (70 mg/kg IP). Normal and AD model groups received also either saline for control or EGCG (10 mg/kg every other day IP) & wheat grass (100 mg/kg PO daily) for treated groups. The brain Aβ, AChE, monoamines, inflammatory mediators, oxidative parameters and brain derived neurotrophic factor (BDNF) were measured. Histopathological examination of brain sections was also conducted. Results: Brain neurological damage is more severe in isolation-associated AD. Treatment of EGCG and wheatgrass together with mental and physical activities (Ph & M) showed higher protection against hazards of AlCl3 and isolation than mental & physical activities alone especially in isolated groups. Their protection was indicated by the significant decrease in Aβ, AChE, MDA, TNF-α, IL-1β together with the increase in SOD, TAC, brain monoamines, BDNF which confirmed by improvement in histopathological pictures of brain sections. Conclusion: It was concluded that, EGCG and wheatgrass together with mental and physical activities can protect against neuronal degenerations associated with the development of AD particularly in social isolated conditions than mental and physical activities alone.